An investigation into the protein composition of the teneral Glossina morsitans morsitans peritrophic matrix. - Clair Rose; Rodrigo Belmonte; Stuart D Armstrong; Gemma Molyneux; Lee R Haines; Michael J Lehane; Jonathan Wastling; Alvaro Acosta-Serrano (Public Library of Science (PLoS), 2014)
Tsetse flies serve as biological vectors for several species of African trypanosomes. In order to survive, proliferate and establish a midgut infection, trypanosomes must cross the tsetse fly peritrophic matrix (PM), which is an acellular gut lining surrounding the blood meal. Crossing of this multi-layered structure occurs at least twice during parasite migration and development, but the mechanism of how trypanosomes do so is not understood. In order to better comprehend the molecular events surrounding trypanosome penetration of the tsetse PM, a mass spectrometry-based approach was applied to investigate the PM protein composition using Glossina morsitans morsitans as a model organism.PMs from male teneral (young, unfed) flies were dissected, solubilised in urea/SDS buffer and the proteins precipitated with cold acetone/TCA. The PM proteins were either subjected to an in-solution tryptic digestion or fractionated on 1D SDS-PAGE, and the resulting bands digested using trypsin. The tryptic fragments from both preparations were purified and analysed by LC-MS/MS.Overall, nearly 300 proteins were identified from both analyses, several of those containing signature Chitin Binding Domains (CBD), including novel peritrophins and peritrophin-like glycoproteins, which are essential in maintaining PM architecture and may act as trypanosome adhesins. Furthermore, 27 proteins from the tsetse secondary endosymbiont, Sodalis glossinidius, were also identified, suggesting this bacterium is probably in close association with the tsetse PM.To our knowledge this is the first report on the protein composition of teneral G. m. morsitans, an important vector of African trypanosomes. Further functional analyses of these proteins will lead to a better understanding of the tsetse physiology and may help identify potential molecular targets to block trypanosome development within the tsetse.